2021
DOI: 10.1111/gcb.15552
|View full text |Cite
|
Sign up to set email alerts
|

Vital roles of soil microbes in driving terrestrial nitrogen immobilization

Abstract: Nitrogen immobilization usually leads to nitrogen retention in soil and, thus, influences soil nitrogen supply for plant growth. Understanding soil nitrogen immobilization is important for predicting soil nitrogen cycling under anthropogenic activities and climate changes. However, the global patterns and drivers of soil nitrogen immobilization remain unclear. We synthesized 1350 observations of gross soil nitrogen immobilization rate (NIR) from 97 articles to identify patterns and drivers of NIR. The global m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 56 publications
2
48
0
Order By: Relevance
“…The PCHCU had the longest N release period, allowing for the longest duration of plant‐available N to be captured on the IEM. Microbial growth and activity can affect the turnover and organic matter mineralization, which can regulate the inorganic N pool (Chen et al., 2018; Li et al., 2021). Furthermore, PCHCU was found to increase microbial activity by 30% and 68% and the amount of potential N mineralization by 5% and 59% compared with urea and the nontreated control, respectively (Lindsey et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCHCU had the longest N release period, allowing for the longest duration of plant‐available N to be captured on the IEM. Microbial growth and activity can affect the turnover and organic matter mineralization, which can regulate the inorganic N pool (Chen et al., 2018; Li et al., 2021). Furthermore, PCHCU was found to increase microbial activity by 30% and 68% and the amount of potential N mineralization by 5% and 59% compared with urea and the nontreated control, respectively (Lindsey et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The PCHCU had the longest N release period, allowing for the longest duration of plant-available N to be captured on the IEM. Microbial growth and activity can affect the turnover and organic matter mineralization, which can regulate the inorganic N pool (Chen et al, 2018;Li et al,…”
Section: Crop Sciencementioning
confidence: 99%
“…Soil microbes are very sensitive to environmental changes and can be used as an indicator of soil quality (Z. Li et al., 2021); their community composition and activity could indicate the element cycles of natural ecosystems, which play important roles in improving soil fertility and restoring the positive succession of ecosystems (L. Zhou et al., 2015). A previous study showed that biochar addition has positive effects on soil microbes (Prayogo et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Strong nitrification may result in surplus NO 3 − in soil, which is susceptible to loss by leaching or denitrification and causes both economic and environmental problems (Subbarao et al, 2006). However, microbial N immobilization is of great importance because it incorporates N into microbial biomass and reduces the risk of reactive N being lost to the environment (Nascente et al, 2021;Z. L. Li et al, 2021).…”
Section: Effects Of Exogenous Organic C On N Transformationsmentioning
confidence: 99%